An early warning system to predict the house price bubbles - Christian Dreger; Konstantin A. Kholodilin (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
In this paper, we construct the country-specific chronologies of the house price bubbles for 12 OECD countries over the period 1969:Q1- 2010:Q2. These chronologies are obtained using a combination of a fundamental and a filter approaches. The resulting speculative bubble chronology is the one that provides the highest concordance between these two techniques. In addition, we suggest an early warning system based on three alternative approaches: signalling approach, logit and probit models. It is shown that the latter two models allow much more accurate predictions of the house price bubbles than the signalling approach. The prediction accuracy of the logit and probit models is high enough to make them useful in forecasting the future speculative bubbles in housing market. Thus, our method can be used by the policymakers in their attempts to timely detect the house price bubbles and attenuate their devastating effects on the domestic and world economy.
Keywords: C25; C33; E32; E37; 330; house prices; early warning system; OECD countries; Immobilienpreis; Bubbles; Prognoseverfahren; Frühwarnsystem; OECD-Staaten